Peran Elit Muhammadiyah Kota Palembang pada Pilkada Tahun 2008 - WALIADIN, AMALIATUL (Politeia: Jurnal Ilmu Politik, 2013)
This is a study about the role of elite Muhammadiyah in Palembang in Local Election 2008. This study is using political behavior approach. Method of data collection using field studies (in-depth interview). Data analysis is using quantitative and qualitative method. The findings of this study that local election as one of the momentum of political contestation at the local level, especially the role of local elites Muhammadiyah Palembang. However, most of the local elite Muhammadiyah does not participate actively sponsoring candidate local elections (Walikota and Wakil Walikota Palembang) 2008-2013. Only a small part is doing it. This study describe that it is difficult to separate the interests of the local elite who linkages actively participating as a team succeed or else toward the Muhammadiyah organization in the city of Palembang. This is because they activity always giving effect to the Muhammadiyah. There is a great potential of the organization Muhammadiyah as a community organization that has a lot of mass.Keywords: Local election, elite, political participation.